Pengaruh Penggunaan Media Sosial dan Kontrol Diri Terhadap Perilaku Konsumtif Mahasiswa di Surakarta (Jurnal Riset Manajemen dan Akuntansi, 2025)
This study aims to determine the influence of social media and self-control on the consumer behavior of students living in Surakarta. The type of research applied is a quantitative method by distributing questionnaires to students as respondents to collect data. The analysis conducted applies validity tests, reliability, basic assumptions, multiple linear regression, t-test, F-test, and coefficient of determination (R²) with the help of SPSS 25. The test results in the study show that social media partially has a positive but not significant effect on the consumer behavior variable, while the self-control variable has a positive and significant effect on the consumer behavior variable. Simultaneously, both independent variables have a significant effect on the consumer behavior of students living in Surakarta, but the effect is not too strong because the questionnaire results show a low level of consumerism in respondents. Therefore, it can be concluded that students living in Surakarta are able to use social media wisely and are able to control themselves so as not to cause consumer behavior in each individual.